Analisis Kebutuhan Media Pembelajaran Digital Bagi Peserta Didik Jenjang SMP - Kurniasih, Tintin; Jaya, Surya; Suyidno, Suyidno; Fahmi, Fahmi (Universitas Sarjanawiyata Tamansiswa, 2024)
The importance of using digital technology in this era is closely related to how the education system runs and applies digital technology. Even in the 21st century learning is very closely linked to the use of digital media to be able to improve high-level skills that are really needed. So it is necessary to analyze the existing needs to improve students' digital literacy which is still low. Based on the questionnaire provided, it shows that the frequency of borrowing digital books and accessing digital-themed media is the lowest at 2.18. It is very necessary to develop authentic learning-oriented e-modules to increase students' digital literacy